Pluralism in "Old Societies and New States": Emerging ASEAN Contexts by Amyn B. Sajoo. Singapore: Institute of Southeast Asian Studies, 1994, pp. 103. (American Journal of Islam and Society, 1997)
Pluralism has emerged as an important aspect of political life since the adventof liberal democracy. It is considered essential for the success of modem states.It indicates the existence of vaiious conflicting ideologies, conception .. values.and purposes of human life at a social level and the plurality of autonomousgroups and organizations at a political level. The existence of modem tates andthe uccessful operation of democracy depends upon how they accommodateethno-cultural diversities within the broad framework of their social ethos and how they develop state mechanisms to safeguard the interests of all groups toensure the well-being of the masses.The book under review describes, in a limited manner, the features and problemsof pluralism in Southeast Asia. The region exhibits the traits of a pluralsociety where different groups and communities live side by side, maintainingtheir separate identities. Cultural interaction and civilized dialogue take placewithout major tension. The countries of the region, particularly members ofASEAN, have concentrated their efforts on economic development and proceededalong the path of industrialization as a means to that. They have succeededin their attempt and distinguished themselves from other countries in thecontinent ...